Sex Differences in the Effect of Type 2 Diabetes on Major Cardiovascular Diseases: Results from a Population-Based Study in Italy - Paola Ballotari; Francesco Venturelli; Marina Greci; Paolo Giorgi Rossi; Valeria Manicardi (International Journal of Endocrinology)
The aim of the study is to assess sex difference in association between type 2 diabetes and incidence of major cardiovascular events, that is, myocardial infarction, stroke, and heart failure, using information retrieved by diabetes register. The inhabitants of Reggio Emilia (Italy) aged 30–84 were followed during 2012–2014. Incidence rate ratios and 95% confidence intervals were calculated using multivariate Poisson model. The age- and sex-specific event rates were graphed. Subjects with type 2 diabetes had an excess risk compared to their counterparts without diabetes for all the three major cardiovascular events. The excess risk is similar in women and men for stroke (1.8 times) and heart failure (2.7 times), while for myocardial infarction, the excess risk in women is greater than the one observed in men (IRR 2.58, 95% CI 2.22–3.00 and IRR 1.78, 95% CI 1.60–2.00, resp.; P of interaction <0.0001). Women had always a lesser risk than men, but in case of myocardial infarction, the women with type 2 diabetes lost part of advantage gained by women free of diabetes (IRR 0.61, 95% CI 0.53–0.72 and IRR 0.36, 95% CI 0.33–0.39, resp.). In women with type 2 diabetes, the risk of major cardiovascular events is anticipated by 20–30 years, while in men it is by 15–20.